Analysis of dose history and health of radiation workers in radiology installation of PKU Muhammadiyah Hospital Bantul and Panti Nugroho Hospital Sleman - Salman, Alfarizi Nursan; Asih Puji, Utami; Retno, Wati (Faculty of Medicine, 2026)
The Radiology Department is a vital unit in hospitals that provides diagnostic and interventional services. However, exposure to ionizing radiation poses health risks for radiation workers. To ensure their safety, regular radiation dose monitoring and health examinations are necessary. This study aims to analyze the radiation dose history and health status of workers in the Radiology Department of RS PKU Muhammadiyah Bantul and RS Panti Nugroho Sleman. Methods: This study employed a qualitative method with a descriptive approach. Data were collected through observation, interviews, literature studies, and documentation from 12 radiographers and 1 radiologist at RS PKU Muhammadiyah Bantul, and 6 radiographers at RS Panti Nugroho Sleman